Securitisation and Desecuritisation of Violence in Trusteeship Statebuilding. Issue 4 (2nd October 2018) - Bonacker, Thorsten; Distler, Werner; Ketzmerick, Maria
ABSTRACT: The United Nations has engaged in (neo)trusteeship statebuilding in two different contexts: post-Second World War decolonisation and after the Cold War. On both occasions, statebuilding aimed at preventing organised, large-scale violence. Nevertheless, these statebuilding efforts were confronted by several forms of violence, ranging from civil war to a high level of politically motivated violence. In this article, we ask how and why administrations in French Cameroon, New Guinea, Kosovo and Timor-Leste implementing (de)securitised such violence – by addressing it as a serious threat and imple-menting policies of protection, by portraying it as something manageable or even by ignoring it.